IMPLEMENTATION OF COMMUNITY NURSE CARE BEHAVIOR TOWARDS COVID-19 REACTIVE SELF-Isolation PATIENTS AT LAWIR PUSKESMAS IN 2021 - Handi, Heribertus; Henny Mariati, Lusia; Dewiyanti Wea, Lidwina; Romana Iwa, Kornelia; Fariday Dewi, Claudia; Y. Demang, Fransiska; Masri Rada, Egis; Roida Eka, Angelina (LPPM Univ. Ibn Khaldun Bogor, 2022)
Community service program for nursing study program lecturers with the theme